Antibiotic Resistance and New Therapeutic Approaches: A Modern Crisis and Pathways Forward - Alwahramadan alghamdi,; Sultan Awadh Ruddah Alharthi,; Abdullh Jemman Abdullah,; Majed Salem Maghib,; Sultan Mohammad Abdullah,; Turki Dakhilallah Alghamdi,; Mohammad Salem Saleh,; Ali Serhan Alghamdi,; Khalaf Abdulaziz Khalaf Albaqqar,; Asma Omar Alhelabi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Consequences of the fast evolution of antibiotic-resistant bacteria include longer hospital stays, more medical costs, and higher death. Globally, this phenomena represents a serious threat to public health. The acceleration of this occurrence resulting from the overuse and abuse of antibiotics in medical and agriculture is making current treatments less effective. This review explores new therapeutic approaches including immune-based strategies, phage therapy, and new drugs as well as the molecular foundations of antibiotic resistance. Taken all together, these programs highlight how important it is to keep researching antibiotics and to utilize them sensibly to help to preserve life. A major public health issue, antibiotic resistance compromises the effectiveness of therapies for bacterial diseases worldwide. The concerning rise in this issue is covered in this paper. Along with the procedures producing resistance and their implications for healthcare, we also address new antibiotics, combination therapies, and other approaches including phage therapy and immunomodulation.